Kinetic Evidence for Type-II Heterojunction and Z-Scheme Interactions in g-C3N4/TiO2Nanotube-Based Photocatalysts in Photocatalytic Hydrogen Evolution - Wang, Yunfei; Fiaz, Muhammad; Kim, Jina; Carl, Nkenku; Kim, Yu Kwon (ACS Applied Energy Materials, 2023)
Composite materials based on g-C3N4 and TiO2 nanotubes have been synthesized as environmentally friendly photocatalysts with heterojunctions suitable for enhanced photocatalytic hydrogen production. Composites were prepared with various ratios (x = 0-1) of g-C3N4 and after chemical modification and exfoliation of bulk g-C3N4. Contact formation between g-C3N4 and TiO2 generally enhanced photoactivity, which caused the x-dependent changes in the photocatalytic hydrogen evolution rates of the g-C3N4/TiO2 compounds to vary following a volcano-shaped curve with the maximum rate at x ∼0.6 for all the compounds regardless of the pretreatment (bulk or modified) of g-C3N4. The modified g-C3N4-based composites showed higher photoactivities than the unmodified bulk g-C3N4 due to the high surface area. The major reason for the enhanced photoactivity with the volcano shape was attributed to the Z-scheme interaction at the heterojunction. Interestingly, detailed analysis of the kinetic H2 evolution rates of the composites with Pt cocatalysts only on TiO2 nanotubes further showed that the dominant type of interaction at the heterojunctions changed from the type-II heterojunction to the Z-scheme at x ∼0.1. It is inferred that structural diversity at the g-C3N4/TiO2 interfaces is the origin of the changes in the dominant type of interaction in the composites with increasing ratios of g-C3N4.
Keywords: Composites material; G-C3N4; Kinetic evidence; Material-based; Photo-activities; Photocatalytic hydrogen evolution; Photocatalytic hydrogen production; TiO 2 nanotube; Type II heterojunction; Z-scheme; g-C3N4; photocatalysis; photocatalytic hydrogen production; TiO2nanotubes; type-II heterojunction; Z-scheme